Local government involvement in post-pandemic development initiatives for the Lao Khrang Ethnic Group of Nakhon Pathom Province - Pratum, Tiranan; Sinthusakun, Pongsai; Tonthongkam, Kengkard (Interdisciplinary Research Review, 2022)
This mixed-methods study examines the role of social enterprises among the Lao Khrang ethnic group in Nakhon Pathom Province. There is particular emphasis placed on the relationship between government agencies and local community leaders. Results were gathered from document analysis and field investigation in five districts of Nakhon Pathom Province, Thailand. Surveys, interviews, and focus-group discussions were the primary research methods. Results reveal that there is a strong community spirit among the Lao Khrang people of Nakhon Pathom. They are involved in the upkeep of traditional culture and participate in the local tourism sector. There has been past government involvement in the maintenance of culture for the benefit of tourism, although this has been put on hold during the current pandemic. This paper argues for a stronger relationship between local government organizations and community leaders to promote sustainability in post-pandemic society.